HEALTH EMERGENCIES POST COVID-19: WHAT GUIDANCE CAN AFRICA’S DISABILITY PROTOCOL PROVIDE? (African Disability Rights Yearbook, 2021)
Several African countries recorded their first cases of the coronavirus disease (COVID-19) in March 2020, the same month the World Health Organisation (WHO) declared it a global pandemic. Within three months the virus has spread throughout the continent. By 29 December the Africa Centres for Disease Control and Prevention put the total number of COVID-19 cases in Africa at 2.6 million with 63 300 deaths recorded. Though there are no official statistics on the number of persons with disabilities in Africa who have tested positive for or succumbed to COVID-19, the Working Group on The Rights of Older Persons and People with Disabilities in Africa in its statement on International Day of Persons with Disabilities acknowledged the potential heightened vulnerability of persons with disabilities on the continent to the pandemic reiterating that many persons with disabilities have pre-existing health conditions that may make them more susceptible to contracting the virus and experiencing more severe symptoms, leading to elevated mortality rates. The discussion that follows focuses on aspects of the monitoring report related to gaps in the protection of right to health of persons with disabilities in Africa during the pandemic. The commentary will use the survey results to illustrate how the Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Persons with Disabilities in Africa (African Disability Protocol), once in effect, may provide additional guidance to states in responding more effectively to the health needs of persons with disabilities during possible further ‘surges’ of the COVID-19 pandemic as well as future health care emergencies. It concludes with a call for African states to expediently ratify the African Disability Protocol so it can come into force.
Keywords: protection of right to health; COVID-19; vulnerability of persons with disabilities